ANALISIS BIAYA PRODUKSI DAN NILAI TEGAKAN PENGUSAHAAN HUTAN ALAM : Kasus suatu perusahaan di propinsi sumatera selatan - Rachman Effendi; Yetti Setyowati; Tien Wahyuni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The main source of revenue for forestry development up to now still depends on natural forest which is the main source of wood for the industries. In the utilization of natural forest the assessment of stumpage value is important to determine the profit margin that goes to goverment as well as to the concession holder.The objective of this study is to get clear picture on the cost components of forest concession and to know the stumpage value of forest land. To determine the stumpage value a production cost analysis was done based on a year operation of concession holder.The results showed that the cost components of log production consists of planning, building main road and skidding road, road maintenance and log houling with total production cost Rp. 58.480,- per m3 for felled area of 1000 ha with production of meranti and mixed species each 22.003,47 m3 and 7. 720, 78 m3, respectively. Based on profit ratio 35% which went to concession holder there is still surplus which the goverment presently does not collect as forest owner. Based on this result goverment revenue in the forms of forest product fee, reforestation fund and concession fee can be increased up to 200% from present level.Key Word : Natural Forest, Stumpage Value, Forest Concession, Production Cost, Forest Product Fee, Reforestation Fund, Concession Fee.